DIGITAL STORYTELLING IN EFL SPEAKING CLASSES: STUDENTS’ PERCEPTIONS AND CHALLENGES - Alfa Rizki, Muhamad; Firyal Aisya, Jasmine; Akbar Najib, Fatih; Husna, Nida (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2025)
This study investigates the implementation of Digital Storytelling (DST) in EFL speaking classes by examining students’ perceptions, experiences, and challenges, as well as its role in supporting linguistic and affective aspects of speaking development. Grounded in persistent EFL speaking difficulties such as anxiety, low confidence, and limited opportunities for meaningful oral practice, this study addresses gaps in previous DST research that has largely focused on narrative outcomes or quantitative performance gains. Using a descriptive mixed-method research design, data were collected through exploratory questionnaires from 20 English Education students engaged in DST-based speaking activities and analyzed descriptively using frequency and thematic analysis. The findings show that DST positively influences students’ speaking development, particularly in confidence, fluency, and motivation, as opportunities to rehearse, and revise speech reduce anxiety and increase awareness of language use. The multimodal features of DST also support clearer idea organization and expression in both narrative and non-narrative speaking tasks. Despite these benefits, students faced challenges related to technical limitations, time constraints, and idea generation. Overall, the study concludes that DST is an effective and flexible instructional approach for enhancing EFL speaking skills when supported by adequate scaffolding, technical assistance, and preparation time.